2021
DOI: 10.1002/smll.202101393
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Enhanced Mass Transfer and Catalytic Production of Sulfate Radicals in MOF‐Derived CeO2 • Co3O4 Nanoflowers for Efficient Degradation of Antibiotics

Abstract: Antibiotics discharge has been a critical issue as the abuse in clinical disease treatment and aquaculture industry. Advanced oxidation process (AOPs) is regarded as a promising approach to degrade organic pollutants from wastewater, however, the catalysts for AOPs always present low activities, and uncontrollable porosities, thus hindering their further wider applications. In this work, an aliovalent‐substitution strategy is employed in metal‐organic framework (MOF) precursors assembly, aiming to introduce Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…[ 106 ] For instance, calcination of Ce/Co–tetrakis(4‐carboxyphenyl)porphyrin frameworks (TCPP) MOFs under air flow creates CeO 2 /Co 3 O 4 heterostructure with nanoflowers‐like architecture inheriting from MOF. [ 107 ] Owing to the ordered architecture, the CeO 2 /Co 3 O 4 have abundant active sites for activation of peroxymonosulfate (PMS), creating a large number of sulfate radicals (SO 4 • − ) for the degradation of antibiotics in environment ( Figure a). [ 108 ]…”
Section: Sacrificial Templating For Assembly Of Ordered Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 106 ] For instance, calcination of Ce/Co–tetrakis(4‐carboxyphenyl)porphyrin frameworks (TCPP) MOFs under air flow creates CeO 2 /Co 3 O 4 heterostructure with nanoflowers‐like architecture inheriting from MOF. [ 107 ] Owing to the ordered architecture, the CeO 2 /Co 3 O 4 have abundant active sites for activation of peroxymonosulfate (PMS), creating a large number of sulfate radicals (SO 4 • − ) for the degradation of antibiotics in environment ( Figure a). [ 108 ]…”
Section: Sacrificial Templating For Assembly Of Ordered Heterostructuresmentioning
confidence: 99%
“…Reproduced with permission. [ 107 ] Copyright 2021, Wiley‐VCH. b) TEM and c,d) HRTEM images of CuO/MgO/Al 2 O 3 heterostructure.…”
Section: Sacrificial Templating For Assembly Of Ordered Heterostructuresmentioning
confidence: 99%
“…The catalytic performance of a single component catalyst is usually lower than that of a synergistic multicomponent catalyst. 28,29 CeO 2 has a high oxygen storage and release capacity. 30,31 However, the catalytic activity of CeO 2 is low owing to its poor oxidation efficiency at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al showed that the strength of the metal–oxygen bond determines the nature of the oxygen species produced and that the Co–O bond is weakened by controlling the pyrolysis temperature, which increases the number of reactive oxygen species. The catalytic performance of a single component catalyst is usually lower than that of a synergistic multicomponent catalyst. , CeO 2 has a high oxygen storage and release capacity. , However, the catalytic activity of CeO 2 is low owing to its poor oxidation efficiency at low temperatures. Some studies have suggested that introducing other active metals can optimize the valence state of electrons, resulting in a strong interaction between the two metal oxides, which is conducive to increasing the density of active sites.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Persulfate-based advanced oxidation processes (PS-AOPs) represent a powerful technique to generate various ROS. 3 Activation and cleavage of peroxide O-O bonds in peroxymonosulfate (PMS) through an energy transfer or reductive electron transfer process can generate reactive species. 4 However, the oxidation efficiency of AOP systems based on radical reaction pathways is very susceptible to the background interference of inorganic anions and organic pollutants in commercial water treatment technologies.…”
mentioning
confidence: 99%